2014
DOI: 10.1155/2014/760393
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Dry Deposition Velocity and Friction Velocity over Different Surfaces for PM2.5 and Particle Number Concentrations

Abstract: Dry deposition of particles is an important way of aerosol removal from the atmosphere and a key process in surface-atmosphere exchanges. The deposition velocities, Vd, are often parameterised in air quality and climate modelling as function of the friction velocity,u*, atmospheric stability, and particle size (if size-segregated information is available). In this work, a study of the correlation between Vd andu*over different surfaces is presented for both PM2.5 and particle number fluxes. Results indicate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…We note that the studies by Möller and Schumann (1970) and Sehmel et al (1974) were conducted in the wind tunnels, and thus the observed deposition does not necessarily reflect deposition under natural conditions. Particle deposition measurements on ice/snow pack were collected from eight studies: Ibrahim et al (1983), Duan et al (1988), Nilsson and Rannik (2001), Gronlund et al (2002), Contini et al (2010), Held et al (2011a, b), and Donateo and Contini (2014). The parameterizations were fed using reported values of particle properties (diameter and density), meteorological conditions (stability parameter, temperature, wind speed, etc.…”
Section: An Evaluation Of the Dry Deposition Parameterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the studies by Möller and Schumann (1970) and Sehmel et al (1974) were conducted in the wind tunnels, and thus the observed deposition does not necessarily reflect deposition under natural conditions. Particle deposition measurements on ice/snow pack were collected from eight studies: Ibrahim et al (1983), Duan et al (1988), Nilsson and Rannik (2001), Gronlund et al (2002), Contini et al (2010), Held et al (2011a, b), and Donateo and Contini (2014). The parameterizations were fed using reported values of particle properties (diameter and density), meteorological conditions (stability parameter, temperature, wind speed, etc.…”
Section: An Evaluation Of the Dry Deposition Parameterizationsmentioning
confidence: 99%
“…Two studies over snow (Ibrahim et al, 1983;and Duan et al, 1988) and six studies over ice surfaces (Nilsson and Rannik, 2001;Gronlund et al, 2002;Contini et al, 2010;Held et al, 2011a, b;and Donateo and Contini, 2014) were used to evaluate the accuracy of the four parameterizations (Z01, PZ10, KS12, and ZH14) for smooth surfaces. The ZS14 parameterization was not included here because it does not allow prediction of deposition over ice/snow surfaces.…”
Section: Evaluation Of Dry Deposition To Snow and Ice Surfacesmentioning
confidence: 99%
“…Actually, for the particle diameter and the free-stream velocity under investigation, Re p and Stokes numbers for the on-scale canyon are expected to be much higher than those characteristics of full-scale canyon, but still lower than 1: then the particle aerodynamics effect in scaling the results proposed in the present paper could be negligible for the idealized fluid dynamic field under investigation. Anyway, the authors point out that atmospheric boundary layer flow scenario could affect the particle deposition velocities [73][74].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For at least 1 km in all directions, the area was characterized by clumps of trees (5-10 m tall), small buildings and internal campus roads. The site had a displacement height of 6.1 m (±0.4 m), and the roughness length was 0.53 m (±0.02 m) [22]. The measurement campaign was performed from 13 to 31 July 2010, mainly during daytime unstable atmospheric conditions.…”
Section: Site Descriptionmentioning
confidence: 99%